Generation of functioning nephrons by implanting human pluripotent stem cell-derived kidney progenitors - Bantounas, Ioannis; Ranjzad, Parisa; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Silajdžić, Edina; Forster, Duncan; Asselin, Marie-Claude; Lewis, Philip; Lennon, Rachel; Plagge, Antonius; Wang, Qi; Woolf, Adrian S.; Kimber, Susan J. (Elsevier, 2018)
Human pluripotent stem cells (hPSCs) hold great promise for understanding kidney development and disease. We reproducibly differentiated three genetically distinct wild-type hPSC lines to kidney precursors that underwent rudimentary morphogenesis in vitro. They expressed nephron and collecting duct lineage marker genes, several of which are mutated in human kidney disease. Lentiviral-transduced hPSCs expressing reporter genes differentiated similarly to controls in vitro. Kidney progenitors were subcutaneously implanted into immunodeficient mice. By 12 weeks, they formed organ-like masses detectable by bioluminescence imaging. Implants included perfused glomeruli containing human capillaries, podocytes with regions of mature basement membrane, and mesangial cells. After intravenous injection of fluorescent low-molecular-weight dextran, signal was detected in tubules, demonstrating uptake from glomerular filtrate. Thus, we have developed methods to trace hPSC-derived kidney precursors that formed functioning nephrons in vivo. These advances beyond in vitro culture are critical steps toward using hPSCs to model and treat kidney diseases.